Exploring the attitudes of solid organ transplant recipients towards COVID-19 shielding communications and the language of ‘clinically extremely vulnerable’: a qualitative study investigating lessons for the future - Jason Ali; Dominic Summers; Abbie E Greig; Kirsten L Rennie (BMJ Public Health)
Introduction Solid organ transplant (SOT) recipients were among the first individuals in the UK identified as ‘clinically extremely vulnerable’ (CEV) to COVID-19 and asked to ‘shield’ at the beginning of the pandemic in March 2020. This qualitative study explores the attitudes of SOT recipients towards COVID-19 shielding communications and the language used.Methods Semistructured interviews were conducted with 43 adult heart, liver and kidney transplant recipients in England between January 2022 and May 2023. Open-ended questions enabled participants to fully explore their experiences of the pandemic and how they felt towards the shielding advice they received. Interviews were transcribed, anonymised and thematically analysed and coded using NVivo V.12.Results Communications about shielding evoked significant fear and anxiety among participants. These communications were perceived as implying that death was probable, or even inevitable, should they leave their home or fail to follow the official advice. Participants expressed widespread dislike for the term ‘CEV’, with the word ‘vulnerable’ being particularly difficult for participants to accept owing to its connotations of weakness and the reminder that participants were not as ‘normal’ as they typically felt. While shielding restrictions have come to an end, longer term impacts were highlighted by participants who expressed ongoing anxiety, with many still choosing to shield and wear a mask if in public.Conclusions This study suggests that governments and health authorities should carefully consider how they communicate with individuals with underlying health conditions in future public health emergencies. We have developed recommendations for how to improve shielding communications in the future, including replacing the phrase ‘CEV’ with that of ‘higher risk’, avoiding using those at higher risk as a national benchmark for risk of illness and death and providing more balanced and engaged communication and advice that takes into consideration the importance of mental well-being.